Isolation, transcription, and inactivation of the gene for an atypical alkaline phosphatase of Synechococcus sp. strain PCC 7942. - Ray, J M (1991)
The alkaline phosphatase of Synechococcus sp. strain PCC 7942 is 145 kDa, which is larger than any alkaline phosphatase previously characterized and approximately three times the size of the analogous enzyme in Escherichia coli. The gene for the alkaline phosphatase, phoA, was cloned and sequenced, and the protein that it encodes was found to have little similarity to other phosphatases. Some sequence similarities were observed between the Synechococcus sp. strain PCC 7942 alkaline phosphatase, the alpha subunit of the ATPase from bacteria and chloroplasts, and the UshA sugar hydrolase of E. coli. Also, limited sequence similarity was observed between a region of the phosphatase and a motif implicated in nucleotide binding. Interestingly, although the alkaline phosphatase is transported across the inner cytoplasmic membrane and into the periplasmic space, it does not appear to have a cleavable signal sequence at its amino terminus. The half-life of the mRNA encoding the alkaline phosphatase, measured after inhibition of RNA synthesis, is approximately 5 min. Similar kinetics for the loss of alkaline phosphatase mRNA occur upon the addition of phosphate to phosphate-depleted cultures, suggesting that high levels of this nutrient inhibit transcription from phoA almost immediately. The phoA gene also appears to be the first gene of an operon; the largest detectable transcript that hybridizes to a phoA gene-specific probe is 11 kb, over twice the size needed to encode the mature protein. Other phosphate-regulated mRNAs are also transcribed upstream of the phoA gene. Insertional inactivation of phoA results in the loss of extracellular, phosphate-regulated phosphatase activity but does not alter the capacity of the cell for phosphate uptake.